The structure of regulatory competition : corporations and public policies in a global economy - Murphy, Dale D. (O.U.P. OxfordGB, 2004)
Identifies cases in cross-border trade and investment with the potential for competition among regulatory jurisdictions. Notes that the policy outcomes of this competition vary and proposes three (related) causes of these divergent outcomes.